Analisis Struktur dan Pola Kalimat pada Karangan Anak Penyandang Tunagrahita Sedang IQ 40-50: Kajian Sintaksis - Muhammad Ramdlan Al-Mubarrok; Wagiati Wagiati (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study is entitled Analysis of Sentence Structure and Patterns in the Writing of Children with Moderate Intellectual Disabilities IQ 40-50: Syntax Study. The purpose is to determine the writing ability of children with mental retardation by analyzing structure and pattern of sentences obtained from them essays. The data in this study were obtained using listening techniques and skillful fishing techniques. The method used is the orthographic equivalent method. In addition, researchers also used the Distribusional Agih method with the BUL technique. Sources of data obtained in this study came from students of Purnama Asih Special School, people with moderate mental retardation with an average IQ of 40-50 as informants. The results showed that the types of writing for children with mental retardation included single sentences, equivalent compound sentences, and multilevel compound sentences. Equivalent compound sentences and multi-level compound sentences often appear imperfectly.